Enhancement of basic properties of polysaccharide-based composites with organic and inorganic fillers: a review - H. P. Shawkataly, Abdul Khalil; Chong, E. W. N.; Taiwo, Owolabi Folahan Abdulwahab; Mustapha, Asniza; Tye, Ying Ying; Rizal, Samsul; M. R., Nurul Fazita; M. K., Mohamad Haafiz; Z., Nurmiati; Md. Tahir, Paridah (John Wiley & Sons, 2019)
The global shift towards biodegradable composite has made polysaccharides a green alternative to synthetic polymers owing to their biocompatibility, sustainability, and ecofriendly biomaterials. Despite the limitations in their applications, many studies have validated the effectiveness of using organic or inorganic fillers to ameliorate their mechanical and barrier properties. However, the understanding of how polysaccharides matrix is enhanced by fillers is still inexplicit. Hence, it is imperative to review the effects of using inorganic and organic fillers in some prominent polysaccharides in terms of mechanical and water barrier properties while taking into account the function of filler morphology, size and loading. Although it is intricate to indicate the best filler used for each of the polysaccharides matrices, this review served as a “food for thought” on the established works of enhanced-matrix filler combinations aimed at improving the mechanical and barrier properties of biodegradable films based on neutral or negatively charged polysaccharides-based composite films for potential application in food packaging, agriculture, biomedicine and constructions sector.